Olympiad movement as a method of training high-level professional competencies - V. I. Prosyanik; O. V. Serebryakova; D. M. Serkin; I. K. Bogomolova (Кардиоваскулярная терапия и профилактика, 2023)
This paper shows the influence of students’ participation in the Olympiad movement in internal medicine on the development of their competencies. On the basis of the Department of Hospital Therapy and Endocrinology of the Chita State Medical Academy, an intra-university Olympiad in internal medicine was held for sixth-year students. We assessed the level of effectiveness of the competence-based approach as part of the active implementation of the Olympiad movement. This paper shows that participation in the Olympiad movement allows students to master a high level of competencies, form a clearer idea of the profession, which in the future makes it possible to prevent professional incompetence.